The Phenomenon of Underage Motorbike Riders in Junior High School Students: A Critical Review of Juvenile Delinquency - Azri Zulfikar Lutfi (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2020)
Motorbike use by students who are under the age of 17 years is an act of infringement. It is stated in Article 281 of Law Number 22 Year 2009 regarding Traffic and Road Transportation. Traffic violations is often done by junior high school students. User behavior motorbikes under the age is a form known as juvenile delinquency. In this study, researcher took samples at two schools namely SMPN 1 Bambanglipuro and SMPN 2 Sanden, Bantul, because researcher saw a lot of students who ride the motorbike to go to school. To examine this phenomenon, researchers used quantitative research methods by taking 394 students as respondents. Associated with the phenomenon of motorbike users under age, this paper focuses on a form of parenting from their parents and motorbike users under age as the dependent variable and independent variables. In this study, the researcher used chi square test to look at the relationship between the independent variable and the dependent variable. This paper uses the concept of social control theory of Travis Hirschi (2007) to understand how such behavior could occur. Indeed the respondents knew what they were doing was a violation, but because of the environment that tends to allow these actions to make them feel safe. As the results obtained in this study, the high number of motorbike users in this study, due to several reasons, namely, less strict parents of children, lack of maintenance performed by local traffic police, and the lack of public attention to such behavior.